PseudoILVEN. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case report. From the first year we followed an 11 year old boy who suffered from verrucous epidermal nevus of the right lower limb. The family history was positive for atopy, in particular the sister was affected by asthma and the brother by atopic dermatitis. Up to the age of 10 years (Fig. 2) the lesion was asymptomatic, but from the last year the child presented intense itching localized mainly around the nevus. The physical examination showed crusted and exuding lesions on the entire nevus, especially at the level of the dorsum of the foot, distributed symmetrically around the nevus (Fig. 1); there were also minimal eczematous palmoplantar lesions. The prick tests showed immediate type sensitization to mites of the genus Dermatophagoides. The patch tests revealed a delayed type sensitization to mercury, in the absence of a clinical history demonstrating its pathogenic role. We diagnosed perinevic atopic dermatitis and prescribed topical corticosteroid therapy which led to remission of the symptoms.